Social media use, social identification and cross-cultural adaptation of international students: A longitudinal examination - Gaitán-Aguilar, Leonor; Hofhuis, Joep; Bierwiaczonek, Kinga; Carmona, Carmen (Frontiers in Psychology, 2022)
The mobility experience is an important life event for international students, and achieving successful psychological and sociocultural adaptation is crucial for this experience to be positive. Through a three-wave longitudinal study among international students enrolled at universities in Spain, Portugal, and Poland (n = 233), we examined the relationships between social media use, social identification, and (sociocultural and psychological) adaptation across time. Results of cross lagged panel modeling (CLPM) showed that social media contact with home nationals predicted greater identification with this group. Social media contact with host country nationals predicted poorer adaptation. Social media contact with other international students did not show any effects, while identification with this group predicted better adaptation. Our results point to the dynamic nature of the adaptation process, showing that the role of social media use and identification targeted at different social groups may play different roles than was previously found in cross-sectional research.